AB0759 FOUR-YEAR EFFICACY AND SAFETY OF GUSELKUMAB IN PSORIASIS PATIENTS WITH AND WITHOUT PSORIATIC ARTHRITIS: A POOLED ANALYSIS FROM VOYAGE 1 AND VOYAGE 2. (2nd June 2020) - Reich, K.; Dutz, J.; Foley, P.; Thaçi, D.; Vender, R.; Song, M.; Miller, M.; You, Y.; Li, S.; Shen, Y. K.; Armstrong, A.
Abstract : Background: Guselkumab (GUS), a fully human monoclonal antibody, selectively binds and blocks interleukin-23. VOYAGE 1 and VOYAGE 2 are two ongoing Phase 3, randomized, double-blind, placebo (PBO)/active comparator-controlled clinical trials of GUS in patients (pts) with moderate-to-severe psoriasis (PsO). Objectives: This post-hoc analysis reports pooled results through 4 years among a subgroup of moderate-to-severe PsO pts with self-reported psoriatic arthritis (PsA) at baseline. Methods: 1829 pts were randomized to GUS 100 mg at Weeks (Wks) 0, 4, and 12, then every 8 wks (q8wk); PBO at Wks 0, 4, and 12, GUS at Wks 16 and 20 then q8wk; or adalimumab (ADA) 80 mg at Wk 0, 40 mg at Wk 1, then 40 mg q2wk until Wk 47 (VOYAGE 1) or Wk 23 (VOYAGE 2). In VOYAGE 1, all pts received open-label GUS 100 mg q8wk during Wks 52-204. VOYAGE 2 incorporated a randomized withdrawal study design, followed by open-label GUS during Wks 76-204. Pooled subgroup analyses using the combined GUS group were conducted based on self-reported PsA status at baseline. Efficacy based on Investigator Global Assessment (IGA) score and Psoriasis Area and Severity Index (PASI) response was assessed using prespecified treatment failure rules (nonresponder status for all time points after discontinuing due to lack of efficacy, worsening of PsO, or use of a prohibited treatment). Results: For pooled VOYAGE 1 and VOYAGE 2 pts (N=1721), combined GUS and ADA to GUS response rates at Wks 100, 156, and 204 were: PASI 90 80.6%, 80.0%, and 80.4%; PASI 100 50.1%, 49.9%, and 52.2%; IGA 0/1 83.6%, 83.3%, and 81.7%; and IGA 0 54.3%, 52.9%, and 53.9, respectively. In the pooled subgroup analysis of pts with and without PsA, response rates were similar across the Wk 100, Wk 156, and Wk 204 evaluations (Table). Rates of adverse events through Wk 204 were comparable for pts with PsA vs those without PsA at baseline. Conclusion: Among GUS-treated pts with moderate-to-severe PsO with and without self-reported PsA at baseline, stable, durable, and high levels of skin responses, as well as comparable safety outcomes, through 4 years were observed. Acknowledgments: None Disclosure of Interests: Kristian Reich Grant/research support from: Janssen Research & Development, LLC, Jan Dutz Grant/research support from: Janssen Research & Development, LLC, Peter Foley Grant/research support from: Janssen Research & Development, LLC, Diamant Thaçi Grant/research support from: Janssen Research & Development, LLC, Ronald Vender Grant/research support from: Janssen Research & Development, LLC, Michael Song Employee of: Janssen Research & Development, LLC, Megan Miller Employee of: Janssen Research & Development, LLC, Yin You Employee of: Janssen Research & Development, LLC, Shu Li Employee of: Janssen Research & Development, LLC, Yaung-Kaung Shen Employee of: Janssen Research & Development, LLC, April Armstrong Grant/research support from: Janssen Research & Development, LLC